PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MASALAH OPEN-ENDED UNTUK MEMFASILITASI KEMAMPUAN BERPIKIR KRITIS SISWA - Suci Rifa Ananda; Atma Murni; Maimunah Maimunah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to produce learning tools (syllabus, lesson plans, and LAS) based on open-ended problems on the material of Constructing Flat Side Space (BRSD) that are valid and practical to facilitate students' critical thinking skills. The 4D development model (Define, Design, Develop, Disseminate) in this study was carried out until small group test of develop stage. The instruments used include: (1) interview guidelines and observation sheets to conduct needs analysis; (2) syllabus, lesson plans, and LAS validation sheets; and (3) student response questionnaires in doing LAS. This study involved three students participating in a one-to-one evaluation and six grade VIII junior high school students as subjects of a small group test and three mathematics education lecturers as validators. The results of the validation of the three validators showed that the syllabus, lesson plans, and LAS were valid with score respectively; 3.6; 3.48; and 3.38. The practicality of LAS shows an average percentage of 86.11% with very practical criteria. The results of this study indicate that the open-ended problem-based learning tool in the material of BRSD is valid and very practical in facilitating students' critical thinking skills.